Consumer Culture Theory (CCT): Twenty Years of Research - Arnould, Eric J.; Thompson, Craig J. (Journal of Consumer Research, 2005)
Abstract This article provides a synthesizing overview of the past 20 yr. of consumer research addressing the sociocultural, experiential, symbolic, and ideological aspects of consumption. Our aim is to provide a viable disciplinary brand for this research tradition that we call consumer culture theory (CCT). We propose that CCT has fulfilled recurrent calls for developing a distinctive body of theoretical knowledge about consumption and marketplace behaviors. In developing this argument, we redress three enduring misconceptions about the nature and analytic orientation of CCT. We then assess how CCT has contributed to consumer research by illuminating the cultural dimensions of the consumption cycle and by developing novel theorizations concerning four thematic domains of research interest.